Análisis del nivel tecnológico de los sistemas de producción del Banano (Musa AAA) en Baba - Solano Ayala, Milton Alfredo (2019)
SUMMARY The present work was carried out in twelve banana plantations belonging to the canton of Baba, province of Los Ríos. The geographic coordinates of the sector evaluated were: 1 ° 47'00.9 "S - 79 ° 41'05.3" W. This shows regular topography and an altitude of 8 masl. The present experimental work is part of a descriptive research, which aims to categorize and compare the technological level in the banana production systems, identifying which of the systems is the most optimal and profitable. The methods of Field Research will be used, which consists in the systematic analysis of problems of reality, with the purpose of either describing them, interpreting them, understanding their nature and constituent factors. It is based on the study that allows the real participation of the researcher or researchers, from the same place where the facts occur, the problem, the phenomenology under consideration. Cluster Banano AS (2016) mentions the Ecuadorian production grew due to the application of new technologies. These tools allowed, minimize the amount of resources used in the processes. For example, thanks to irrigation systems, drainage, and cableways (which facilitate the transfer of banana), you can count on a single worker per hectare that produces 3 thousand boxes of bananas, while in the old systems, too Traditional calls, it needed up to five workers per hectare that produced an average of 1,000 boxes. A general diagnosis was made that includes basic indicators of the implementation of the technology in areas of the field, management in the plantation and in the packing area with particular depth in the technology of the banana plantations, for which the survey technique, using as a tool a questionnaire applied to the owners or managers of the selected banana plantations.